2017
DOI: 10.1371/journal.pone.0181172
|View full text |Cite
|
Sign up to set email alerts
|

The utility of measles and rubella IgM serology in an elimination setting, Ontario, Canada, 2009–2014

Abstract: In Canada, measles was eliminated in 1998 and rubella in 2000. Effective measles and rubella surveillance is vital in elimination settings, hinging on reliable laboratory methods. However, low-prevalence settings affect the predictive value of laboratory tests. We conducted an analysis to determine the performance of measles and rubella IgM testing in a jurisdiction where both infections are eliminated.21,299 test results were extracted from the Public Health Ontario Laboratories database and 1,239 reports wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…2 , 92 In the absence of clinically compatible symptoms or a clear epidemiological link to a laboratory-confirmed case, false-positive IgM results are common. 2 , 92 Thus, it is important to restrict laboratory testing to persons likely to have measles (e.g., those with a febrile rash illness and risk factors such as travel or being unvaccinated) and to obtain routinely specimens for RT-PCR testing along with serological samples. 1-3 In this context, when confirming a diagnosis of measles with a positive IgM, Canada has specified the requirement of an appropriate exposure (epidemiological-link to another case or travel history), in addition to measles-compatible symptoms.…”
Section: Exclusion Measures Among Exposed Individuals Who Received Apmentioning
confidence: 99%
See 2 more Smart Citations
“…2 , 92 In the absence of clinically compatible symptoms or a clear epidemiological link to a laboratory-confirmed case, false-positive IgM results are common. 2 , 92 Thus, it is important to restrict laboratory testing to persons likely to have measles (e.g., those with a febrile rash illness and risk factors such as travel or being unvaccinated) and to obtain routinely specimens for RT-PCR testing along with serological samples. 1-3 In this context, when confirming a diagnosis of measles with a positive IgM, Canada has specified the requirement of an appropriate exposure (epidemiological-link to another case or travel history), in addition to measles-compatible symptoms.…”
Section: Exclusion Measures Among Exposed Individuals Who Received Apmentioning
confidence: 99%
“…1-3 In this context, when confirming a diagnosis of measles with a positive IgM, Canada has specified the requirement of an appropriate exposure (epidemiological-link to another case or travel history), in addition to measles-compatible symptoms. 2 , 92 Conversely, because measles is rare in elimination settings, suspected cases with a positive IgM necessitate detailed epidemiological investigations for an unrecognized exposure, and they may require additional diagnostic testing before being ruled out. 2 , 4 , 92 …”
Section: Exclusion Measures Among Exposed Individuals Who Received Apmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon initial activation B cells produce IgM and during further differentiation could undergo class switch recombination resulting in the production of IgG or IgA ( Figure 1). Therefore, detecting specific IgM can be an indication of recent exposure to a pathogen or antigen of a pathogen [51,52]. For most vaccines, especially vaccines administered intramuscularly, the majority of B cells will switch toward the production of IgG [53].…”
Section: The Immunobiology Behind Serosurveysmentioning
confidence: 99%
“…Mucosal vaccination or infection will also induce IgA (not depicted). Changes in pathogens related to antigenic drift/shift, or immunity/vaccine escape and rubella indicated that this approach is insufficient to assess new infections [51]. Moreover, the kinetics of IgM induction following exposure to a new pathogen may also change with age, as observed in a novel influenza infection in the USA, where young individuals induced IgM whereas older individuals showed no significant changes in IgM production, probably due to cross-reactive antibodies to previously encountered influenza viruses [75].…”
Section: Antibody Levels and Aviditymentioning
confidence: 99%